Assessing the cytotoxic/genotoxic activity and estrogenic/antiestrogenic potential of essential oils from seven aromatic plants. (April 2020) - Contini, Adele; Di Bello, Domenica; Azzarà, Alessia; Giovanelli, Silvia; D'Urso, Giuseppina; Piaggi, Simona; Pinto, Barbara; Pistelli, Luisa; Scarpato, Roberto; Testi, Serena
Abstract: Alternative therapies with new drugs are needed because the clinical efficacy of conventional chemotherapy is often reduced due to collateral effects. Many natural products of plant origin, including essential oils (EOs) have proved to be effective in prevention and therapy of several diseases such as bacterial infections, chronic diseases and cancer. In the present study, we investigated some biological activities of EOs extracted from seven plants: Rosmarinus officinalis, Salvia somalensis, Thymus vulgaris, Achillea millefolium, Helichrysum italicum, Pistacia lentiscus, Myrtus communis . In particular, we evaluated the cytotoxic and genotoxic activity using the cytochalasin B-blocked micronucleus assay (CBMN) in human peripheral lymphocytes, cytotoxicity in a human ovarian carcinoma cell line (A2780), and the estrogenic/antiestrogenic activity using a yeast strain expressing the human estrogen receptor alpha (ERα). Our results show that most EOs can have a strong cytotoxic and a slight/moderate genotoxic effect on human peripheral lymphocytes, and also a pronounced cytotoxic effect in A2780 cells. In addition, some EOs seem to have a marked antiestrogenic activity that could potentially perturb the estrogen-dependent tissues. Highlights: Evaluation of cyto-genotoxic and anti-estrogenic activity of seven essential oils. EOs analyzed are moderately genotoxic on human peripheral lymphocytes. Some EOs induce cytotoxicity on peripheral lymphocytes and A2780 human cell line. Some EOs interact with the human ERα resulting in a marked antiestrogenic activity.